α Cell Function and Gene Expression Are Compromised in Type 1 Diabetes - Brissova, Marcela; Haliyur, Rachana; Saunders, Diane; Shrestha, Shristi; Dai, Chunhua; Blodgett, David M.; Bottino, Rita; Campbell-Thompson, Martha; Aramandla, Radhika; Poffenberger, Gregory; Lindner, Jill; Pan, Fong Cheng; et al. (Cell reports (Cambridge), 2018)
Many patients with type 1 diabetes (T1D) have residual β cells producing small amounts of C-peptide long after disease onset but develop an inadequate glucagon response to hypoglycemia following T1D diagnosis. The features of these residual β cells and α cells in the islet endocrine compartment are largely unknown, due to the difficulty of comprehensive investigation. By studying the T1D pancreas and isolated islets, we show that remnant β cells appeared to maintain several aspects of regulated insulin secretion. However, the function of T1D α cells was markedly reduced, and these cells had alterations in transcription factors constituting α and β cell identity. In the native pancreas and after placing the T1D islets into a non-autoimmune, normoglycemic in vivo environment, there was no evidence of α-to-β cell conversion. These results suggest an explanation for the disordered T1D counterregulatory glucagon response to hypoglycemia. [Display omitted] •T1D β cells appear to maintain several aspects of regulated insulin secretion•T1D α cells have impaired glucagon secretion and altered gene expression•Unlike in rodents, α-to-β cell conversion in human T1D is a very rare event•T1D α cell identity factors improve in a non-autoimmune, normoglycemic environment Brissova et al. find that β cells in the type 1 diabetic (T1D) pancreas maintain several functional and molecular features, but α cells have impaired glucagon secretion and an altered gene expression profile. These findings provide insight into the mechanism of α cell dysfunction in T1D.